Study on Overburden Failure and Surface Sinkhole Development Law during Extra-Thick Coal Seam Mining beneath Thick Unconsolidated Layers - Huang, Zhenzhen (International Journal of Natural Resources and Environmental Studies, 2026)
To address the problem of surface collapse and sinkhole disasters induced by fully mechanized top-coal caving mining of extra-thick coal seams beneath thick unconsolidated layers, the F6204 working face of Buliangou Coal Mine was selected as the engineering background. Field investigation, theoretical analysis, and numerical simulation were employed to investigate the evolution characteristics of overburden failure and the formation mechanism of surface sinkholes. The results indicate that the overburden structure of the F6204 working face is mainly composed of a “loess layer–conglomerate–basalt” assemblage, in which the basalt stratum acts as the primary key stratum. After coal extraction, a distinct “three-zone” overburden structure is formed. With the increase in mining thickness, the stability of the beam-arch structure in the overburden gradually decreases. Once the basalt primary key stratum fractures, surface collapse and sinkhole disasters are likely to occur. When the coal seam thickness exceeds 15 m, surface deformation gradually transforms from continuous subsidence to discontinuous stepped collapse. Based on these findings, a control technology combining high-level key stratum presplitting and separation-layer grouting is proposed, which can effectively mitigate surface sinkhole hazards. The research results can provide a reference for the safe and efficient mining of extra-thick coal seams under similar geological conditions.